2019
DOI: 10.1007/s10661-019-7843-z
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of microplastic pollution: occurrence and characterisation in Vesijärvi lake and Pikku Vesijärvi pond, Finland

Abstract: In the last few years, several studies have investigated microplastics (MPs) in marine ecosystems, but data monitoring and assessing the occurrence in freshwater environments are still scarce. The present study aims to investigate the occurrence, distribution, and chemical composition of MP pollution in Vesijärvi lake and Pikku Vesijärvi pond close to the city of Lahti (Finland) in winter. Sediment, snow, and ice core samples were collected near the shore of these two aquatic systems. MPs were analysed and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 67 publications
4
35
1
2
Order By: Relevance
“…Due to its ubiquitous use, low cost, and the single-use throwaway culture, plastic pollution has become a severe environmental problem [2]. Plastic debris as a source of waste and chemical pollution is detected not only in oceans, forming huge swirling patches in areas, but also soil, sediment, freshwater bodies, and even human stool [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its ubiquitous use, low cost, and the single-use throwaway culture, plastic pollution has become a severe environmental problem [2]. Plastic debris as a source of waste and chemical pollution is detected not only in oceans, forming huge swirling patches in areas, but also soil, sediment, freshwater bodies, and even human stool [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…MPs are being detected in nearly all ecosystems across the globe (Barnes et al 2009;Lusher et al 2015;da Costa et al 2016;Imhof et al 2017;Ng et al 2018;Peeken et al 2018;Scopetani et al 2019), including the water column and sediments of many aquatic environments (Browne et al 2010;Claessens et al 2011;Naidoo et al 2015;Reisser et al 2015;Hoffman and Hittinger 2017). There is a consensus among the scienti c community that even though plastic pollution in aquatic ecosystems is recognised as an environmental threat, data on the ecotoxicity of plastics are scarce (Eerkes-Medrano et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The MPs (4 mm particles) used were high-density polyethylene (HDPE) (confirmed by Fourier-transform infrared (FTIR) and Raman spectra) produced from threaded bottle caps-common trash seen globally. The MP type, size, and concentration were selected based on monitoring studies which reported on MP pollution in sediments, considering the most commonly detected MPs and their abundance and size distribution [16,17]. In addition, the size used (4 mm) was explicitly selected by selective sieving, so that the pieces would be too large to be consumed by the Enchytraeids.…”
Section: Introductionmentioning
confidence: 99%